Plan de negocios para la creación de una empresa especializada en la fabricación y distribución de productos embutidos a base de pescado en la ciudad de Santa Marta (2023)
The present work demonstrates the viability of the creation a small-sized company created as a simplified joint-stock company dedicated to the manufacture and distribution of fish slices using bonefish as a base, characterized by its high nutritional values and aimed at all people. Who like this protein carrier especially those who seek 100% natural food. The project is created by the motivation to exploit the resources that the region possesses and thus contribute to boosting the economy, providing benefits to the authors as owners of the idea, fishermen in the region due to the marking that contracts the search for raw material and other direct and indirect collaborators that are required for the elaboration and distribution of the product. This business proposal is based on the idea of building a process of elaboration and distribution of fish-based meat products, showing the ease and the little time spent in preparation and that serves as an ideal companion, highlighting its nutritional benefits, managing to be part of diet people in general. The following document will implement a mixed type of research, using qualitative and quantitative recognition tools, in order to make use of the instruments of a primary and secondary nature, seeking the global analysis of the object of study. At the institutional level, this research is developed following the line of the Innovation Management area